Analisis Rasio Profitabilitas Sebagai Alat Ukur Kinerja Keuangan PT Bank Central Asia - Lailatus Sa’adah; Muhammad Rifqy Nurarifin; Nur Aidah Fitriana (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to analyze financial performance using profitability ratios in banking companies (Study at PT. Bank Central Asia (Persero) Tbk in 2018-2020). The sample of this study was taken from the Bank Central Asia company. Financial report data was obtained from the Indonesia Stock Exchange (IDX). The method used in this study is a qualitative analysis method. The results of this study indicate that the company's financial performance is in good condition when viewed through the NPM, ROA, and ROE ratios.